Extraction Methods and Implementation Technologies of Fuel Injection Pump Cam Profile Characteristics. (31st March 2021) - Liu, Yangpeng; Chen, Peng; Ding, Jianjun; Sun, Lin; Li, Tao; Li, Changsheng; Guo, Jingyang; Song, Mingming; Jiang, Zhuangde
Abstract : Because the traditional camshaft measurement methods cannot be applied to the injection pump cam, in order to improve the measurement automation of injection camshaft, an accurate extraction method of the characteristic parameters of the injection cam profile is proposed in this paper. In this method, the phase error optimization is realized by the angle precise rotation matching of the actual lift data. The optimization is realized by the Lagrangian polynomial interpolation algorithm based on the moving window. The goals of precise measurement of the peach point phase of single high point cam and accurate acquisition of the back dead point phase of high point arc segment cam are realized. Compared with the precision of high-precision measuring equipment, the method can extract the lift and phase angle error of the cam accurately and stably.